2021
DOI: 10.3389/fendo.2021.742089
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Follicle-Stimulating Hormone Alfa Dose Adjustment in US Clinical Practice: An Observational, Retrospective Analysis of a Real-World Electronic Medical Records Database

Abstract: PurposeTo determine the pattern of dose adjustment of recombinant human follicle-stimulating hormone alfa (r-hFSH-alfa) during ovarian stimulation (OS) for assisted reproductive technology (ART) in a real-world setting.MethodsThis was an observational, retrospective analysis of data from an electronic de-identified medical records database including 39 clinics in the USA. Women undergoing OS for ART (initiated 2009–2016) with r-hFSH-alfa (Gonal-f® or Gonal-f RFF Redi-ject®) were included. Assessed outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A potential limitation of the study is that adjustments in rhFSH dose were permitted during COS (38), with adjustments limited to 50 IU. The dose adjustment of rhFSH is part of daily clinical practice during COS, and a systematic review covering 10 years showed that the proportion was about 45% (39).…”
Section: Pregnancy and Birth Outcomesmentioning
confidence: 99%
“…A potential limitation of the study is that adjustments in rhFSH dose were permitted during COS (38), with adjustments limited to 50 IU. The dose adjustment of rhFSH is part of daily clinical practice during COS, and a systematic review covering 10 years showed that the proportion was about 45% (39).…”
Section: Pregnancy and Birth Outcomesmentioning
confidence: 99%
“…Dosing may then be adjusted during the cycle or in subsequent cycles depending on patient response. The approach of individualizing gonadotropin doses in OS for IVF is common in clinical practice across the US and occurs more often in younger versus older patients ( 17 ), and has demonstrated comparable efficacy and increased safety compared with conventional fixed dosing ( 14 ). However, there is a lack of corresponding data on gonadotropin dose adjustments in OI/OS for timed intercourse or IUI.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of gonadotropin starting doses and dose adjustments occurred in 40.7% of cycles during OS for assisted reproductive technology, according to one report of real-world data ( 17 ), and in up to 45% of patients during OS for IVF, according to a recent systematic review of clinical studies ( 1 ). However, the prevalence and magnitude of dose adjustments in OI/OS for timed intercourse or IUI, and the clinical characteristics and demographics of patients undergoing OI/OS for timed intercourse or IUI with gonadotropins receiving dose adjustments have not, to the best of our knowledge, been assessed in real-world databases.…”
Section: Introductionmentioning
confidence: 99%